Influence of plant growth regulators on growth of Scots pine seedlings in open ground (in Kyiv Forest Research Station) - Savuschyk, M. P.; Khromulyak, O. I.; Shlonchak, G. A.; Yashchuk, I. V. (Forestry and Forest Melioration, 2020)
Introduction Plant growth regulators are gradually entering the forestry business. It primarily occurs due to a decrease in the production of high-quality planting material in nurseries. The latter is often associated with signs of a progressive decline in soil fertility. Conducted research has testified the efficiency of growth regulators application when cultivating planting material. Their use effects significantly the whole process, starting from the stage of seed preparation for sowing. Therefore, the search for modern effective plant growth regulators is relevant. Materials and Methods The study was conducted at the nursery of the Kyiv Forest Research Station. Plant growth regulators Epin Extra, Humate Ultra, Megafol and Stimpo were used in the tests. Tthe effect of plant growth regulators on seeds was investigated using pre-sowing treatment in aqueous solutions of the studied products. When growing pine seedlings, plant growth regulators were used for spraying and watering. Results Pre-sowing treatment with plant growth regulators affected the quality of Scots pine seeds. Among the others, Epin Extra and Stimpo increased germination energy. The most noticeable effect was in the version of Stimpo. The increase made 38% compared to control. Seed germination increased compared to control in Epin Extra and Stimpo variants by 5 and 13% respectively. The tested plant growth regulators affected significantly the growth rates of the grown pine seedlings. The maximum excess of height over control was obtained with the Megafol variant. The average height of the planting material was 13.9 cm. The minimum height was 8.4 cm in control. In experimental variants, the minimum value of height when using Stimpo was 9.9 cm. Megafol-fed seedlings had the longest roots. The average values ??reached 30.5 cm, in the control they were 22.2 cm. In all 4 variants of plant growth regulators, the diameter of the root collar of seedlings statistically exceeded the control. The biggest excess showed the Megafol variant. A calculation of the number of side shoots of seedlings showed that none of the options had a significant excess. The average weight of the aboveground part of one seedling statistically exceeded the control in the experimental versions of Megafol and Epin. The needle proportion in the mass of the aboveground part of the seedlings significantly exceeded control when using Megafol. Megafol had a statistically significant maximum excess of the mass of the roots of the experimental seedlings over the control. Other options are important at the control level. Air-dry weight of the aboveground part of 1-year-old seedlings varies greatly in the options of the experiments. All experimental variants exceeded control seedlings. The maximum value of the aboveground part was noted when using the Megafol regulator. Conclusions 1. Pre-sowing treatment with plant growth regulators affects the quality of Scots pine seeds. Among the others, Stimpo showed the most stimulating effect for the germination of Scots pine seeds. 2. Feeding plant material with plant growth regulators contributed to the increase of their biometric and weight indicators. Megafol showed the maximum probable excess of height, diameter of a root collar, length of roots and average weight of seedlings over control. 3. The conducted research has testified that it is efficient to apply Stimpo and Megafol when cultivating pine planting material. 5 Tables, 10 Refs. Key words: Pinus sylvestris L., plant growth stimulants, pine seeds, planting material.